Application of dynamic thermal imaging in a photocarcinogenesis mouse model. (3rd October 2018) - Baek, Yoo Sang; Kim, Jaeyoung; Han, Geo; Oh, Chil Hwan
Abstract: Introduction: In clinical practice and experimental settings, cutaneous premalignant and malignant lesions are commonly diagnosed by histopathological biopsy. However, this technique is invasive and results in functional or cosmetic defects. Dynamic thermal imaging is a non-invasive technique that quantifies the infra-red (IR) radiation emitted by a subject after the introduction of external thermal stimuli (such as heat or cold). Methods: Forty hairless albino (Crl:SKH1-hr) mice were randomised to the control group or the experimental group. The experimental group was regularly irradiated with artificial ultraviolet. Clinical photographs, immunohistochemical staining and dynamic thermal imaging results of both groups were obtained. Results: As photocarcinogenesis proceeded, faster thermal recovery to basal temperature after heat stimuli was significant on dynamic thermal imaging. With histopathological correlations, it was possible to differentiate normal, premalignant and malignant cutaneous lesions according to thermal imaging results. CD 31 staining analysis showed that increased vasculature was the key change responsible for different thermal imaging results among photocarcinogenesis steps. Conclusions: Dynamic thermal imaging is useful to differentiate normal, premalignant and malignant cutaneous lesions. Increased vasculature is the key change responsible for different thermal imaging results.